A motivação de alunos do ensino fundamental de uma escola pública de Belo Horizonte para aprender Ciências na perspectiva de uma sequência de ensino investigativo - Sérgio Geraldo Torquato de Oliveira (2017)
This research focused on a concern of teachers and researchers of basic education about the motivation of students of basic education to learn scientific concepts. To investigate such disquiet, the following question was posed: Can the Inquiry Teaching Learning of Science foster students' motivation to learn science and maintain it throughout the course of their learning? To help answer this question, a sequence of research teaching on the Anatomy and Physiology of the Human Digestive System was elaborated, which was also one of the products of this dissertation, with activities that are based on the approach of Science Teaching by Research. In addition to the references Inquiry Teaching Learning of Science, this research was based on the research on Motivation and used the tools of Self-Determination Theory that help in the understanding of the quality of motivation, composing a continuum evaluated by a set of items that includes three types (Knowing, Performing and Experiencing stimuli), to three types of extrinsic motivation (External, Introjection, Identification and Integrated) and Demotivation. The Methodology used for data collection and analysis was qualitative, focused on action research. The data collected came from the logbooks of the students and the regent teacher, as well as excerpts from the video recordings of the classes and the students' responses to the extrinsic motivation questionnaire. The data analyzed provided a very promising perspective regarding the motivation of students in the classes conducted in an investigative way. Through the analyzes, it was possible to perceive that this approach evidenced the satisfaction of the basic psychological needs of autonomy, belonging and competence, elements considered necessary to consider that there was motivation of the students to develop the proposed activities in the sequence of teaching. Such perception may allow teachers to use this curricular and methodological proposal to promote and increase the motivation of their students. These data also point to questions about the importance of surveying previous conceptions, the appropriation of scientific concepts as descriptions of the body and the natural world and the importance of reading and writing in science classes.